Solidification/Stabilization Disposal of Medical Waste Incinerator Flyash Using Cement - P., Agamuthu; S., Chitra (Malaysian Journal of Science, 2009)
Medical wastes in Malaysia are incinerated with the ash disposed into landfills. We studied alternative treatments of medical waste incineration fly ash by solidification/ stabilization (S/S) using three types of cement: OPC, MSC and GGBS. The effect of additives - activated carbon (Ac) and rice husk (Rh) on metal retention was also studied. Metal leaching was quantified using TCLP, JLT-13 and ANS 16.1 (modified). Compressibility strength was measured by ASTM (Compressive Strength of Hydraulic Cement Mortars). Ash contained high concentrations of Al, Ti, Fe, Zn, Cr, Fe, Pb and Cu and most of these elements leached heavily if not treated. TCLP and JLT-13 quantification showed all cement types prevented metal leaching. Solidification with Ac and Rh respectively further reduced leached metals by 10 and 20%, resapectively. ANS 16.1 (modified) showed leach rates between 10-4 and 70 cm/day. Leachability Index rates exceeded 6.0, indicating low leaching. Compressive strength increased as cement loading and curing days increased. OPC showed higher metal retention efficiency and compressive strength. Estimated costs for S/S treatment are higher than current disposal costs. However, S/S products could be used as raw materials for construction.